Seasonal variations in ash and alginic acid contents of seaweeds - Rao, C H Kesava (Indian Journal of Fisheries, 2011)
Growth, in terms of unit biomass and alginic acid content, of 3 seaweeds, viz. Cystoseira indica. Sargasstim tenerrimum and S. johnstonii, collected from Porbandar and Okha reefs for one year, was measured. A significant linear relationship between the ash and alginic acid contents on unit biomass basis was observed. However, alginic acid showed inverse relationship with total carbon to ash ratio (C/ash). The unit biomass parameter (weight/height) was advantageous than heigh t alone to explain the seasonal variation of alginic acid with respect to growth in seaweeds. In addition to the cell sap minerals alginates contributed to the ash content. Alginic acid was highest during rapid growth period, followed by the reproductive stage and the lowest in the senescent growth period.